Prividenie, kotoroe ne vozvrashchaetsia . The Ghost that Never Returns - Room, Abram (Sovkino, 1929)
Duration: 00:51:00 Jose Real is a worker at an oil-well who is sent to prison in an unspecified Latin American country for his revolutionary ideas. Because of his charisma and political beliefs, he becomes very popular among the prisoners, while attracting the negative attention of the authorities. The latter decide to elimante him, but with the help of his comrades he will overcome all obstacles in the end. Very strong cinematography, rapid montage and moving story based on a story by Henri Barbusse make for an exciting movie. It´s not a completely silent movie, there is a spoken word every now and then, accompanied by intertitles. In bonus features the DVD contains "Stenka Razine", the first movie made in Russia, in 1908.